(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Pre-service English teachers often lack sufficient opportunities for authentic practice and personalized feedback during their training, hindering the development of essential teaching skills. This paper explores how AI voice agents, like those developed by ElevenLabs, can enhance the teaching competence of future English educators by providing realistic conversational practice, exposure to diverse learners, and instant feedback. AI-powered teaching simulations can supplement traditional teacher preparation, allowing teachers to gain experience adapting their language, pedagogy, and classroom management strategies to various contexts. While more research is needed on the long-term effects of AI-assisted teacher training, initial findings suggest it could significantly improve pre-service teachers’ confidence and adaptability. Realizing the full potential of AI in teacher education will require collaboration among educators, researchers, and AI developers to ensure pedagogically sound, culturally responsive, and ethical implementation. Ultimately, AI has the potential to revolutionize English teacher preparation and better equip future educators for real-world classrooms.